Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/978-3-030-12334-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing Controls: A Review and Research Agenda for Crowdsourcing Controls Used for Macro-tasks

Abstract: Crowdsourcing-the employment of ad hoc online labor to perform various tasks-has become a popular outsourcing vehicle. Our current approach to crowdsourcing-focusing on micro-tasks-fails to leverage the potential of crowds to tackle more complex problems. To leverage crowds to tackle more complex macrotasks requires a better comprehension of crowdsourcing controls. Crowdsourcing controls are mechanisms used to align crowd workers' actions with predefined standards to achieve a set of goals and objectives. Unfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 108 publications
0
13
0
Order By: Relevance
“…Research on behavior controls in virtual teams has focused on whether they facilitate or hinder the development of trust in virtual teams. Research has also demonstrated the potential of controls to alter team members' behavior and attitudes in virtual teams [3,4,13,49], therefore, research is needed to understand the influence that controls can have on social loafing in virtual teams. This study highlights the important role that control can have on reducing social loafing in virtual teams.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Research on behavior controls in virtual teams has focused on whether they facilitate or hinder the development of trust in virtual teams. Research has also demonstrated the potential of controls to alter team members' behavior and attitudes in virtual teams [3,4,13,49], therefore, research is needed to understand the influence that controls can have on social loafing in virtual teams. This study highlights the important role that control can have on reducing social loafing in virtual teams.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the results of this study demonstrate how problematic affect-based trust can be for virtual teams. In addition, much of the research on trust in virtual teams has been directed at understanding how trust can be developed in virtual environments [4,[11][12][13]49]. However, scholars have called for further research on understanding the conditions that determine the effectiveness of trust [17,89].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations